The Vital Role of a Federally Qualified Community Health Center in New Orleans, Louisiana, During the COVID-19 Pandemic. Issue 1 (January 2021) - Halperin, Jason; Conner, Katherine; Telleria, Christian; Agins, Bruce; Butler, Isolde
Abstract : Federally qualified health centers (FQHCs) are on the front lines of the COVID-19 pandemic. Their mission of providing essential medical care to underserved populations is now even more vital. CrescentCare, an FQHC in New Orleans, evaluated and tested 3366 patients between March 16 and July 2, with an overall rate of 12% SARS-CoV-2 positivity. The clinic's experience demonstrates how to effectively and rapidly integrate COVID-19 programing, while preserving essential health services. Strategies include developing a walk-in COVID-19 testing site, ensuring appropriate clinical evaluation, providing accurate public health information, and advocating for job safety on behalf of our patients.